Pengujian Kualitas Website Ditinjau dari Perspektif Accessibility, Experience, Marketing dan Technology - Diyurman Gea (ComTech: Computer, Mathematics and Engineering Applications, 2014)
The purpose of this study was to determine the quality of the websites managed by individuals, companies and governments. The test results would be useful for managers to pay more attention to the quality of the website optimally through several perspectives: accessibility, experience, marketing and technology. The research used samples from 350 websites and the data were divided into seven categories, namely: website managed by SMEs (small and medium), website of universities, website of governments, e-commerce, news websites, website of industrial companies, and website of non-profit organization. We used Nibler as the testing tool to facilitate the assessment process. Data were analyzed using WEKA presented in the form of a decision tree. The results showed that the tested websites had an average value of 4.66 or worse (scale 1-10). The conclusion is that the manager of the website should perform repairs on the data and applications, in particular in the perspective of technology, accessibility and experience.